The Relevance of Monzer Kahf's Views on Islamic Banking in Indonesia - Wijaya, Buana Handa; Dzukha Asyiqin, Akbar; Marno Rahayu, Sherly (Invest Journal of Sharia & Economic Law, 2023)
This article aims to analyze the relevance of Monzer Kahf's view of Islamic banking to the development of Islamic banking in Indonesia, with a particular focus on Bank Syariah Indonesia (BSI). Although Islamic banking has grown rapidly in Indonesia, there are still challenges in understanding the factors that influence its success and how these banks can serve the community more effectively. To achieve this goal, the method used is library research, which aims to collect some information obtained through books, journals and online media that have relevance to the topic with Monzer Kahf's Islamic banking thinking and secondary data on the development of Bank Syariah Indonesia. The results of the analysis show that some of the key factors identified by Monzer Kahf, such as increasing the form of deposits, improving the quality of customer service, expanding the banking service base, capital protection, and providing social and humanitarian services, are very relevant in the context of the development of Islamic banks in Indonesia. Bank Syariah Indonesia, as the largest Islamic bank in Indonesia, plays an important role in driving the country's economic growth. In addition, the bank is also expected to improve its social services to the community through various aspects, including education, health, environment and renewable energy. In conclusion, Monzer Kahf's views on Islamic banking are highly relevant to the development of Islamic banking in Indonesia.